MATERIAL REQUIREMENT PLANNING UNTUK MEMENUHI PRODUKSI PADA CV. BANGUN CIPTA ARTHA DI BADUNG - Yasa, I Made Sugita; Mandala, Kastawan (E-Jurnal Manajemen; Vol 9 No 2 (2020), 2020)
Inventory management without Material Requirement systems in CV. Bangun Cipta Artha resulted in the lot size for each order of raw materials not optimal. One concept that can be used to plan and control raw materials is the Material Requirement Planning. This study is to determine the number of sizes of raw material orders, the exact order time, the method that produces the lowest cost for each raw material, and the effect of using MRP on inventory costs. This research conducted on 160x200cm spring bed products. Data was analyzed by making production master schedules, determining net requirements, determining lot size, and making MRP tables. Based on the results, the determination the best lot sizing is the order quantiy period which results in a total inventory cost of Rp. 26,475,220 where the total cost is lower, compared to lot for lot method which Rp. 43,464,000. part period balancing Rp. 33,106,576, and conventional method Rp.49,472,912. Keywords: Material Requirement Planning (MRP), Sizing Lot, Lot For Lot, Balancing Part Period, Period Order Quantiy